2020
DOI: 10.3390/antiox9121242
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Supplementation Modulates Neutrophil Inflammatory Response to Exercise-Induced Stress

Abstract: The aim of the present report was to evaluate the inflammatory response to a 2000-m running test considering neutrophil myeloperoxidase as an inflammatory marker, and to verify if supplements rich in antioxidants could modulate Post-test antioxidant and anti-inflammatory responses. To this end, a 21-day homogenization period was carried out with three groups: a control group, a supplemented group taking an almond beverage enriched with vitamins C and E and a third group consuming the same beverage but enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…On the other hand, high-intensity eccentric exercises favor exercise-induced muscle damage (EIMD) [ 48 , 55 , 56 , 57 , 58 , 59 ]. EIMD results in elevations of inflammatory markers (i.e., C-reactive protein/CRP) and pro-inflammatory cytokines, including IL-1, IL-6 and TNF-α among others.…”
Section: Exercise and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, high-intensity eccentric exercises favor exercise-induced muscle damage (EIMD) [ 48 , 55 , 56 , 57 , 58 , 59 ]. EIMD results in elevations of inflammatory markers (i.e., C-reactive protein/CRP) and pro-inflammatory cytokines, including IL-1, IL-6 and TNF-α among others.…”
Section: Exercise and Inflammationmentioning
confidence: 99%
“…In order to exert its effect, vitamin D binds to the intracellular receptor VDR [ 57 , 58 ]. VDR–vitamin D complex modulates the expression of hundreds of genes that perform essential functions [ 57 , 58 , 59 , 60 , 61 ]. VDR–vitamin D complex also regulates NO synthesis through endotelial NOS (eNOS) activity [ 60 ].…”
Section: Why Vitamin D Supplements Improve Muscular Damage Recovery?mentioning
confidence: 99%
“…They were then put through a 2000-m running test. The researchers concluded that antioxidant beverages might protect neutrophils from oxidative injury to SM during exercise [70].…”
Section: In Terms Of Inflammationmentioning
confidence: 99%
“…The VDR-vitamin D complex regulates the expression of hundreds of genes that code for proteins that accomplish key cellular functions. In this context, the VDR-vitamin D complex stimulates eNOS expression, regulating at long term the synthesis of NO [107,[110][111][112][113]. Regulated production of NO can promote angiogenesis of endothelial cells [114,115].…”
Section: Vitamin D and The Inflammatory Responsementioning
confidence: 99%